Ultrastructure of spiracles of Musca domestica and Hydrotaea chalcogaster (Diptera: Muscidae) - Sukontason K.L. (2014)
Spiracles are major respiratory openings in the exoskeleton of insects. Oxygen, a necessary gas for cell activity, must pass through the spiracle to enter the respiratory system. In this study, we investigated the fine structure of spiracles of adult females of Musca domestica L. and Hydrotaea chalcogaster (Wiedemann), both medically important fly species in many parts of the world, by utilizing scanning electron microscopy. The mesothoracic spiracle of M. domestica is large and elongate-oval in shape, with its anterior end being gradually tapered. The outer surface is densely covered with slender setae of variable distribution and orientation. The metathoracic spiracle is semicircular or D-shaped, with its rim possessing long, fine, inwardly curved setae. A net-like valve or sieve plate, which has a smooth rim with swollen surface, is located within the atrium of this species. The abdominal spiracles are circular with a symmetrically swollen peritreme surrounding the opening. The inner filtering apparatus is composed of many spiral tubes, each possessing many small spines. As for H. chalcogaster, the tapering mesothoracic spiracle is covered with long setae arranged consistently inward from the peritreme, giving it a "combed" appearance. The metathoracic spiracle is similarly arranged but triangularly rounded in shape, with the anterior and posterior rims possessing long fine setae. The net-like valve within the atrium has a smooth, swollen rim, whereas the inner edge of the atrium bears short, slender setae where it meets with the peritreme of the spiracle. The abdominal spiracles of this species look similar to that of M. domestica, with the exception of the filtering apparatus that bears only a few small spines. The function of these spiracles is discussed. © 2006 Springer-Verlag.